2002
DOI: 10.1104/pp.005439
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transcript Levels of the Arabidopsis Cytochrome P450 Genes Involved in Brassinosteroid Biosynthesis

Abstract: Cytochrome P450 enzymes of the closely related CYP90 and CYP85 families catalyze essential oxidative reactions in the biosynthesis of brassinosteroid (BR) hormones. Arabidopsis CYP90B1/DWF4 and CYP90A1/CPD are responsible for respective C-22 and C-23 hydroxylation of the steroid side chain and CYP85A1 catalyzes C-6 oxidation of 6-deoxo intermediates, whereas the functions of CYP90C1/ROT3, CYP90D1, and CYP85A2 are still unknown. Semiquantitative reverse transcriptase-polymerase chain reaction analyses show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
170
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(195 citation statements)
references
References 40 publications
19
170
1
2
Order By: Relevance
“…Biosynthesis and inactivation are coordinated via BR-dependent transcriptional control of the genes involved in both processes. All BR-biosynthetic P450 genes of Arabidopsis are under negative feedback regulation by active BRs (Bancos et al, 2002;Tanaka et al, 2005), whereas of those encoding inactivating enzymes only BAS1 was found BR inducible (Choe et al, 2001;Takahashi et al, 2005). Feedback regulation of CPD is abolished in the BR-insensitive bin2 and brassinosteroid insensitive 1-2 (bri1-2)/cbb2 mutants (Li et al, 2001;Bancos et al, 2002), indicating a key role of BR signaling in the hormonal self-regulation of BR biosynthesis and perhaps also inactivation.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Biosynthesis and inactivation are coordinated via BR-dependent transcriptional control of the genes involved in both processes. All BR-biosynthetic P450 genes of Arabidopsis are under negative feedback regulation by active BRs (Bancos et al, 2002;Tanaka et al, 2005), whereas of those encoding inactivating enzymes only BAS1 was found BR inducible (Choe et al, 2001;Takahashi et al, 2005). Feedback regulation of CPD is abolished in the BR-insensitive bin2 and brassinosteroid insensitive 1-2 (bri1-2)/cbb2 mutants (Li et al, 2001;Bancos et al, 2002), indicating a key role of BR signaling in the hormonal self-regulation of BR biosynthesis and perhaps also inactivation.…”
mentioning
confidence: 89%
“…Recent studies indicated that in Arabidopsis the expression of all BR-biosynthetic P450 genes is under both developmental and organ-specific regulation that take place primarily at the level of transcription (Bancos et al, 2002;Shimada et al, 2003;Kim et al, 2006). This can influence the efficiency of biosynthesis because activities of certain genes encoding rate-limiting enzymes, such as CPD in Arabidopsis or DWARF/ CYP85A1 and CYP85A3 in tomato, show good correlation with the accumulation of active BRs (Bancos et al, 2002;Montoya et al, 2005;Nomura et al, 2005).…”
mentioning
confidence: 99%
“…Sterols are precursors of brassinosteroids/brassinolides, which are steroid hormones that promote plant growth and cell division, and of steroidal triterpenoids such as the glycoalkaloids in Solanum species [58]. Four P450 families act downstream of CYP51 and CYP710 in brassinosteroid metabolism: CYP85 catalyses C-6 oxidations, whereas CYP90A, CYP90B, CYP90C and CYP90D subfamily members catalyse C-22 and C-23 hydroxylations [59]. Two P450 families are involved in inactivation of brassinosteroids.…”
Section: Recruitment Of P450s For Triterpenoid Biosynthesismentioning
confidence: 99%
“…2 This is consistent with previous studies conducted in Arabidopsis and tomato, where expression levels of selected BR-synthesis genes were also closely correlated with the actual endogenous BR levels. [11][12][13][14] However, this situation did not hold true when we examined the full complement of genes involved in the BR synthesis pathway. Indeed, there were just as many examples where the expression of individual genes did not reflect the endogenous BR levels.…”
mentioning
confidence: 84%